White matter injuries mediate brain age effects on cognitive function in cerebral small vessel disease. - Li, Yuanhao; Tian, Tian; Qin, Yuanyuan; Zhang, Shun; Liu, Chengxia; Zhu, Wenzhen (Neuroradiology, 2025)
Purpose: This study aims to investigate the potential effect of compromised structural integrity on cerebral aging and cognitive function in cerebral small vessel disease (CSVD). Methods: Fifty-five CSVD patients and 42 controls underwent three-dimensional T1-weighted imaging and diffusion tensor imaging. Relative brain age (RBA) was computed to assess cerebral aging. Variables of structural integrity included cortical thickness, cortical volume, white matter hyperintensity (WMH) volume, peak width of skeletonized mean diffusivity (PSMD), ventricular volume, and choroid plexus volume. Mini-Mental State Examination (MMSE) was conducted to assess general cognition. Trail Making Test (TMT) and Auditory Verbal Learning Test were administered to evaluate executive function and episodic memory, respectively. Mediation analysis and multivariate linear regression with interaction terms were performed to explore the differential impacts of RBA on cognitive function and structural integrity between CSVD patients and controls. Results: RBA was significantly increased in CSVD patients compared to controls (p < 0.001). White matter injuries as assessed with PSMD (mediation magnitude: 41.1%) and WMH volume (mediation magnitude: 56.9%) significantly mediated the relationship between CSVD pathologies and RBA (p < 0.001). Higher RBA was significantly correlated with poorer scores of MMSE, TMT-A, and TMT-B in CSVD patients (p < 0.01). Additionally, PSMD (mediation magnitude: 57.8% in MMSE, 48.3% in TMT-A, and 28.8% in TMT-B) and WMH volume (mediation magnitude: 55.1% in MMSE) significantly mediated the relationship between RBA and cognitive function (p < 0.05). Conclusion: White matter injuries play a critical role in the cerebral aging and cognitive decline in CSVD patients.